Recovery Of Titanium Dioxide (Tio2) From The Photocatalysis Process - Tan, Qing Long (Universiti Sains Malaysia, 2022)
Titanium dioxide, often known as TiO2, has been manufactured commercially since the early 20th century. TiO2 is quickly developing into a vast variety of new applications such as ceramic industry, wood preservatives, textile fibre, and printed electronics. In 2021, the price of titanium dioxide has multiplied by eight due to the rising cost of raw materials and huge demand. Furthermore, the manufacture of TiO2 will generate a substantial volume of toxic by-products and waste materials from chloride and sulphate process. Thus, reusability of recovered and regenerated TiO2 is proposed in this research study. The photodegradation efficiency is determined by treating synthetic wastewater sample containing atenolol, carbamazepine, and diclofenac. High-performance liquid chromatography (HPLC) is used in this study for checking the removal efficiency of photocatalyst. Preliminary experiments were conducted to determine effect of adsorption and direct photolysis on fresh TiO2 photocatalyst. Optimum dosage of 0.2 mg/L catalyst loading was implemented for recovered and regenerated photocatalyst experiments. From the results, recovered TiO2 achieve photodegradation of 43.8 % (atenolol), 42.1 % (diclofenac) and 39.5 % (carbamazepine) after the fifth run. Reusing of regenerated TiO2 has higher removal efficiency than recovered TiO2 after four successive cycles. Reuse of photocatalyst TiO2 is applicable for sustainable of environment.